Bilayer membrane with asymmetric wettability based on superhydrophilic/underwater superoleophobic cotton fabric for simultaneous oil-dye-water separation - Luwen Zhao; Yu Xia; Zhi Zhang; Yuan Zhu; Mingzhu Li; Jinlin Shen; Boxuan Zhu; Li Lv; Hongliang Ke; Zaisheng Cai; Yaping Zhao (Journal of Environmental Chemical Engineering, 2026)

Next-generation intelligent prepared aquatic dishes: research progress in digital heat control and quality evaluation empowered by industry 4.0 - Ying Xie; Min Zhang; Qi Yu; Yaping Liu (Food Research International, 2026)

Bamboo cellulose fiber aerogel for radioactive cobalt adsorption with ultimate volume reduction: A green and economic disposal pathway - Hongyan Chen; Zhuo Chen; Zhanquan Wang; Yu Wang; Xinyu Xie; Qin Chen; Jinchao Li; Yaping Zhang; Liang Chen (Chemical Engineering Journal, 2026)

The alkaloid-rich extract of Piper sintenense Hatusima alleviates gouty inflammatory response via Nrf2-mediated antioxidant induction - Zhiren Yao; Yu Su; Yaping Huang; Can Hu; Ke Pan; Jian Zhang; Guoqing Zhao; Lei Wang; Zhiqi Yin (Inflammopharmacology, 2026)

Iron-mediated reversal of humic acid inhibition in anoxygenic photoheterotrophic carbon fixation via redirected electron flux and restored redox homeostasis - Xiaoyan Bai; Ting Yu; Yaping Zhang; Jian Sun; Yong Yuan (Journal of Environmental Sciences, 2026)

Synergistic enhancement of sodium storage in bamboo-derived hard carbon via Ni nanoparticle incorporation and P-doping - Wanquan Liu; Liu Wang; Wenjing Lu; Yong Cheng; Yu Chen; Enze Ren; Zhenyao Wang; Jing Wu; Xinhui Li; Yaping Zeng (Biomass and Bioenergy, 2026)

Coupling near infrared spectroscopy with machine learning algorithms for simultaneously detecting multiple microplastics in soil - Jia Long; Xi Li; Renjie Yang; Guimei Dong; Yaping Yu; Huiyong Shan (Journal of Soils and Sediments, 2026)

SETD2 Improves Endothelial Function and Angiogenesis in Diabetic Hindlimb Ischemia Via Activating ANGPT2-PI3K/AKT Pathway - Langtao Wang; Qing Wang; Jiaxing Duan; Yu Tan; Yuanyuan Liu; Shuai Hu; Cheng Wang; Chen Yang; Yanzhu Long; Jinxuan Wang; Tao Yu; Tianhu Liu; et al. (Cardiovascular Toxicology, 2026)

Seawater acidification accelerates growth but hastens decline in batch cultures of the marine diatom Thalassiosira pseudonana - Haiyang Zong; Zihao Sun; Dongmei Lv; Yu Shang; Yaping Wu; Juntian Xu; Futian Li (Marine Environmental Research, 2026)

Blueberry juice fermented by a high β-glucosidase-producing lactic acid bacterium mitigates skin aging by modulating gut microbiota - Shasha Cheng; Yaqi Liang; Yaping Zheng; Hongxuan Li; Yu Zhang; Yujun Jiang (Food Bioscience, 2026)

A Serpine1-F2-PAR1 axis facilitates apoptosis and disease severity during GCRV infection in grass carp - Yangyang Li; Liangming Chen; Bin Gui; Changchun Yu; Jinyan Lei; Yuxuan Shao; Haiping Liu; Zuoyan Zhu; Yaping Wang; Rong Huang (Fish & Shellfish Immunology, 2026)

UiO-66 porous liquids with synergistic catalytic effects for promoting efficient CO2 conversion - Yaru Lu; Ruyu Bai; Dechao Wang; Yangyang Xin; Weirui Zhang; Fangfang Su; Zheng Dong; Wendi Fan; Yating Zhang; Fangli Yu; Xin Li; Yingying Zhou; et al. (Chemical Engineering Journal, 2026)

Genomic insights into recurrent demographic collapses and recovery dynamics in Tibetan antelopes (Pantholops hodgsoni) - Weimin Kuang; Hongfeng Zhang; Yingli Jiang; Han Hu; Wei Huang; Yaping Zhang; Xiaomin Wu; Li Yu (Science China Life Sciences, 2026)

Spatiotemporal dynamics of microplastics in urban stormwater runoff: Functional area effects and transport pathways (Shanghai, China) - Junhao Li; Bowen Yu; Chengjin Cao; Liuxing Wu; Yaping Zhao; Ruiyun Zhu; Yangyang Hu; Minsheng Huang; Lei Wang; Xinlin Yan (Journal of Contaminant Hydrology, 2026)

Fracture evolution and differential mechanical response of surrounding rock in deep tunnel excavation: A case study under complex geological conditions - Xiaojun Yu; Xizhi Zhang; Xia-Ting Feng; Feiyan Wang; Ming Shi; Chengxiang Yang; Huanzhen Luo; Yaping Yang; Yushan Wang (Engineering Geology, 2026)

Distribution characteristics and controlling factors of Wenchang Formation fan in the Enping 17 Sag steep slope zone, Zhujiang River Mouth Basin - Yaping Sui; Guangrong Peng; Wei Wu; Guangxu Wang; Xiaomeng Wang; Zhendong Feng; Jing Yu; Tao Wan; Weiye Zhao (Acta Oceanologica Sinica, 2026)

A novel retrieval of global dust optical depth and effective diameter based on MODIS thermal infrared observations - Jianyu Zheng; Hongbin Yu; Yaping Zhou; Yingxi Shi; Zhibo Zhang; Claudia Di Biagio; Paola Formenti; Alexander Smirnov (Remote Sensing of Environment, 2026)

A quantitative assessment framework for ship collision risk: Integrating spatiotemporal urgency analysis - Yu Chen Xin; Xiong Guan Bao; Yaping Yang (Ocean Engineering, 2026)

Construction of platinum/cobalt aluminate heterostructured catalyst via spent catalyst recycling for photo-Fenton-like degradation of malathion - Qiancheng Zhou; Jupei Zhang; Qiuhao Shu; Fengshan Yu; Yaping Guo (Journal of Water Process Engineering, 2026)

Grass carp (Ctenopharyngodon idella) Kat5 mediates P53 acetylation to induce apoptosis and promotes GCRV replication - Bao Liu; Chuxin Wu; Xianggao Meng; Tingting Yu; Xucheng Zhang; Jing Liu; Mingzhi Li; Yaping Weng; Huiling Mao; Chengyu Hu; Lingbao Kong; Meifeng Li (Fish & Shellfish Immunology, 2026)

Electrically insulating BNNS/PVDF@AlN/PVP composites with simultaneously enhanced in-plane and through-plane thermal conductivities - Wei-Hua Han; Yaping Fan; Yu Long; Bin Sun; Yun-Ze Long; Chun-Cheng Hao (Chemical Engineering Journal, 2026)

Metabolic engineering of blueberry juice by Lactiplantibacillus plantarum JM065: Fermentation optimization - Shasha Cheng; Yaping Zheng; Hongxuan Li; Yujun Jiang; Yu Zhang (Food Chemistry, 2025)

Highly sensitive and wide-range quantification of bovine αS1-casein in foods for predicting potential milk allergenicity using an IgE multi-epitope-specific antibody - Caiyi Shen; Liming Li; Caiyun Long; Yunbiao Luo; Yaping Dong; Jinyu Yu; Yi Yao; Guanrong Hu; Xin Li; Hongbing Chen; Shengfa He (Food Chemistry, 2025)

Soil and enzymatic C:N:P stoichiometry response to carbon and nutrient input: evidence from long-term fertilization experiments - Qiong Xiao; Yaping Huang; Guoping Chen; Kailou Liu; Yu Jiang; Boku Zhou; Ping Zhu; Xiaori Han; Junyong Ma; Shutang Liu; Shaomin Huang; Aijun Zhang; et al. (Plant and Soil, 2025)

Mo-Nitrogen nexus: Nanotechnology enhanced Mo-based nitrogen fixation towards environmental sustainability - Samina Irshad; Yu Xie; Yaping Lyu; Ziqi Zhang; Xingxin Liu; Haojie Wei; Beza Tuga; Christy L. Haynes; Yaqi Jiang; Yi Sun; Jason C. White; Yukui Rui; et al. (Chemical Engineering Journal, 2025)

Enhanced degradation of 1,2,4-trichlorobenzene by Pd-loaded biochar-supported nZVI: Through a reduction-oxidation coupling process - Wenxuan Luo; Chenghua Xu; Chao Wang; Dandan Yu; Yaping Zhang; Changsheng Qu (Journal of Environmental Management, 2025)

Standardized scale development for fogg behavioral model towards energy-saving behavioral change in buildings - Jiachen Luan; Yaping Zhou; Jun Zhang; Zhun (Jerry) Yu (Energy and Buildings, 2025)

Bio-inspired spore-like CoSe2@CNFs heterostructure enabling ultra-stable and high-rate sodium-ion batteries - Enze Ren; Yu Chen; Yaping Zeng; Zhenyao Wang; Wanquan Liu; Heng Wang; Jianrong Xiao; Liu Wang (Chemical Engineering Journal, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Enhanced short-term prediction of urban PM2.5 concentrations by improved hybrid deep learning - Yin Zhou; Yaping Lyu; Xiuli Dang; Roland Bol; Peng Zhang; Na Yu; Yuling Zhang (Journal of Environmental Health Science and Engineering, 2025)

K-doped LaAlO3 A-sites: Regulating surface basicity and oxygen species composition for highly efficient organosulfur hydrolysis - Jian Gao; Yu Zhou; Bingran Wang; Wenxuan Luo; Peng Wu; Kai Shen; Yaping Zhang (Journal of Cleaner Production, 2025)

Integrated coordination of production scheduling, preventive maintenance, and energy conservation in flexible manufacturing environments - Yu Wang; Tangbin Xia; Yaping Li; Shuo Gao; Dong Wang; Lifeng Xi (Journal of Cleaner Production, 2025)

Screening of siderophore-producing bacteria isolated from marine environments - Xiang Zeng; Guangyu Li; Yaping Du; Tong Yu; Qiliang Lai; Liping Wang; Zongze Shao (Acta Oceanologica Sinica, 2025)

Progress on the mechanism of natural polysaccharides in the treatment of arthritis - Lili Yuan; Michael Adu-Frimpong; Hong Chen; Yaping Yang; Jiangnan Yu; Huiya Wang; Yuxiang He; Elmurat Toreniyazov; Xia Cao; Qilong Wang; Ximing Xu (Inflammopharmacology, 2025)

Enhancing cardiac regeneration: direct reprogramming of fibroblasts into myocardial-like cells using extracellular vesicles secreted by cardiomyocytes - Yao Yao; Yuexin Yu; Yaping Xu; Yingtian Liu; Zhikun Guo (Molecular and Cellular Biochemistry, 2025)

Ghβ-LCY1 influences metabolism and photosynthetic in Gossypium hirsutum - Yanmin Qian; Yaping Wang; Yu Zhang; Zongyan Chu; Mengxin Shen; Cheng Zhang; Lihua Huang; Zhihua Yang; Kaiwen Ren; Yuanyuan Shi; Tingting Jiao; Baoting Yang; et al. (Plant Science, 2025)

Fermentation of soymilk by strains with high conversion ability to soy isoflavones: Strain screening, flavor characteristics, antioxidant properties, and in vitro digestion - Yaping Zheng; Kaiqi Gao; Zimu Li; Yinzhi Zhang; Xuejian Li; Wei Zhang; Ling Guo; Yu Zhang; Yujun Jiang (Food Bioscience, 2025)

Hydrogels in cardiac tissue engineering: application and challenges - Yaping Xu; Yuexin Yu; Zhikun Guo (Molecular and Cellular Biochemistry, 2025)

Microplastics and Dechlorane Plus co-exposure amplifies their impacts on soybean plant - Yu Xie; Junzhe Zhang; Yaping Lyu; Yaqi Jiang; Yi Sun; Ziqi Zhang; Haojie Wei; Xingxin Liu; Yukui Rui; Wenlong Yang; Peng Zhang (Environmental Pollution, 2025)

A new evolutionary topology optimization method for truss structures towards practical design applications - Yaping Lai; Qi Cai; Yu Li; Jiayong Chen; Yi Min Xie (Engineering Structures, 2025)

Silver nanoparticle-functionalized covalent organic frameworks for the inhibition of foodborne pathogenic bacteria and their application in green grape preservation - Jiayi Zhou; Sai Zhang; Yu Zhang; Tianliang Liu; Shuying Yang; Gaopeng Lv; Yaping Wang; Kewei Feng; Yahong Yuan; Tianli Yue; Qinglin Sheng (Food Chemistry, 2025)

Association between blood microplastic levels and severity of extracranial artery stenosis - Hongxiang Yu; Hongxia Li; Can Cui; Yingying Han; Yaping Xiao; Bei Zhang; Gang Li (Journal of Hazardous Materials, 2024)

Selective recovery of platinum from spent catalysts to fabricate platinum/amorphous manganese oxide/corrugated silica carrier for formaldehyde removal - Fengshan Yu; Maolin Tian; Xueli Wang; Wenjie Zhang; Chunxia Wang; Jiawei Wen; Junlian Wang; Yaping Guo; Guoyong Huang (Journal of Environmental Chemical Engineering, 2024)

Sinensetin from citrus peel alleviates DSS-induced inflammation by regulating gut microbiota and serum metabolism in mice - Zuomin Hu; Zhongxing Chu; Xuke Ling; Yuchi Wu; Dandan Qin; Feiyan Yang; Xudong Yu; Yaping Zhou; Yiping Tang; Feijun Luo (Food Bioscience, 2024)

A Q-learning based artificial bee colony algorithm for solving surgery scheduling problems with setup time - Ruixue Zhang; Hui Yu; Kaizhou Gao; Yaping Fu; Joong Hoon Kim (Swarm and Evolutionary Computation, 2024)

Status and trends of artificial intelligence in the R & D of future fruit & vegetable juice - Huanhuan Niu; Min Zhang; Qi Yu; Yaping Liu (Innovative Food Science & Emerging Technologies, 2024)

Enhanced reductive catalytic fractionation of lignocellulose using a water-resistant RuNiZnOx/Nb2O5 catalyst with synergistic hydrogen spillover and acidic properties - Zhaozhuo Yu; Wenzhuo Kong; Yaping Guo; Wen Liang; Jiawei Liang; Meijuan Chen; Dongxu Zhao; Hongzhen Ma; Xiangjun Liu; Solomon Inalegwu Okopi; Lei Che; Qi Zhang; et al. (Fuel, 2024)

Widely metabolomic combined with transcriptome analysis to build a bioactive compound regulatory network for the fruit growth cycle in Pseudocydonia sinensis - Shuangyu Zhang; Yang Wu; Yanshen Ren; Yaping Xu; Hong An; Qianyi Zhao; Yu Wang; Houhua Li (Food Chemistry, 2024)

Rational tailoring of spin-polarized photoelectrode for magnetic-assisted overall water splitting - Kehui Xue; Lianqing Yu; Chong Liu; Huihua Luo; Yaping Zhang; Haifeng Zhu; Wei Xing (Chemical Engineering Journal, 2024)

Different contributions of meteorological conditions and emission reductions to the ozone pollution during Shanghai’s COVID-19 lockdowns in winter and spring - Xuedan Dou; Mengying Li; Yaping Jiang; Zhe Song; Pengfei Li; Shaocai Yu (Atmospheric Pollution Research, 2024)

Therapeutic Effect of Smilax glabra Roxb. on Weaning Rats Against Pb-Induced Nephrotoxicity Based on Network Pharmacology - Chongmei Tian; Meiting Yu; Yuejuan Fang; Yaping Zhao; Liping Fu; Jingbai Chen; Daozong Xia (Biological Trace Element Research, 2024)

A thermo-hydro-mechanical simulation on the impact of fracture network connectivity on the production performance of a multi-fracture enhanced geothermal system - Zhihong Lei; Yulong Zhang; Xingjie Lin; Yu Shi; Yunhui Zhang; Ling Zhou; Yaping Shen (Geothermics, 2024)

Low-humidity sensor and biomimetic power supply based on mesoporous silica/polymerizable deep eutectic solvent ionogels - Zhiyan Ma; Yanyu Cui; Yaping Song; Yunlong Yu; Hongran Zhao; Sen Liu; Xishuang Liang; Teng Fei; Tong Zhang (Chemical Engineering Journal, 2024)

Regional assessment for the occurrence probability of wind erosion based on the joint probability density function of air density and wind speed - Yushi Liang; Yaping Shen; Zeyu Zhang; Xiaodong Ji; Mulan Zhang; Yiran Li; Yu Wang; Xinyue Xue (CATENA, 2024)

Reduction of heavy metal emissions by adding modified attapulgite to sludge in bubbling fluidized bed incineration process - Zhiyao Li; Junfeng Pang; Yu Zhou; Kai Shen; Yaping Zhang (Fuel, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Effect of complex prebiotics on Lactobacillus gasseri JM1 fermented soymilk: Physicochemical, flavor characteristics, and metabolites - Yaping Zheng; Wenfang Wu; Man Zhu; Yilin Sun; Dong Hu; Yujun Jiang; Yu Zhang; Chaoxin Man (Food Bioscience, 2024)

Selenium protects against Pb-induced renal oxidative injury in weaning rats and human renal tubular epithelial cells through activating NRF2 - Chongmei Tian; Yu Qiu; Yaping Zhao; Liping Fu; Daozong Xia; Junjie Ying (Journal of Trace Elements in Medicine and Biology, 2024)

Relationship of environmental exposure temperature and temperature extremes on sperm DNA fragmentation index in men with different BMI values and the indirect effect of DNA fragmentation index on semen parameters - Chen Wang; Qiwei Yu; Ting Chu; Fang Wang; Fangli Dong; Hang Xin; Di Wang; Yaping Liu; Jun Zhai (Science of The Total Environment, 2024)

Cracking formation and evolution in surrounding rock of a deep fractured rock mass roadway: A study of the 790-m level segment engineering at the Jinchuan Mine, China - Xiaojun Yu; Yaping Yang; Xifan Li; Huanzhen Luo; Yushan Wang; Xizhi Zhang; Yongyuan Kou; Hongye Li; Yangyi Zhou (Engineering Geology, 2024)

Different ligand functionalized bimetallic (Zr/Ce)UiO-66 as a support for immobilization of phosphotungstic acid with enhanced activity for the esterification of fatty acids - Qiuyun Zhang; Yaping Wu; Xingyue Hong; Zhenying Li; Yanting Lei; Rongfei Yu; Taoli Deng; Yutao Zhang; Peihua Ma (Sustainable Chemistry and Pharmacy, 2024)

Study on the effect of cyclic catalytic pyrolysis on sludge pyrolysis products - Yan Wu; Yuexin Zhang; Maoqing Wang; Yaping Xia; Guoxin Lan; Bin Yan; Yue Yu; Xinyi Xiong; Junhan Zou; Yin Zhu (Journal of Environmental Chemical Engineering, 2024)

Large contributions of emission reductions and meteorological conditions to the abatement of PM2.5 in Beijing during the 24th Winter Olympic Games in 2022 - Yaping Jiang; Shaocai Yu; Xue Chen; Yibo Zhang; Mengying Li; Zhen Li; Zhe Song; Pengfei Li; Xiaoye Zhang; Eric Lichtfouse; Daniel Rosenfeld (Journal of Environmental Sciences, 2024)

An assessment of natural and anthropogenic influences on atmospheric fluoride deposition in central Tibetan Plateau during 1951–2008 A.D. using the Zangser Kangri ice core - Xiang Zou; Wangbin Zhang; Shuangye Wu; Jinhai Yu; Jing Song; Hongxi Pang; Yaping Liu; Shugui Hou (Atmospheric Environment, 2024)

Constructing a cross-field scenario system to aware systemic risk: national security as an example - Qing Deng; Mengjiao Yao; Hui Zhang; Feng Yu; Lida Huang; Yaping Ma (Natural Hazards, 2024)

Engineered hydrochar from waste reed straw for peroxymonosulfate activation to degrade quinclorac and improve solanaceae plants growth - Chunxia Ding; Can Ye; Wei Zhu; Guangyong Zeng; Xuemei Yao; Yu Ouyang; Jie Rong; Yaping Tao; Xiangying Liu; Yaocheng Deng (Journal of Environmental Management, 2023)

Identification and analysis of alleles in the aroma biosynthesis pathways based on Camellia sinensis ‘Jinguanyin’ haplotype-resolved genomes - Mengya Gu; Ting Gao; Mengting Xu; Yaping Hong; Yibin Wang; Jiaxin Yu; Yuhang Zhang; Wenqin She; Pengjie Wang; Naixing Ye (Trees, 2023)

Impact of the producer services agglomeration on PM2.5: A case study of the Yellow River Basin, China - Yan Liu; Yu Cheng; Ruijing Zheng; Huaxue Zhao; Yaping Wang (Journal of Geographical Sciences, 2023)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

Fine and coarse particulate air pollution and out-of-hospital cardiac arrest onset: a nationwide case-crossover study in China - Chang Pan; Chang Xu; Jiaqi Zheng; Ruixue Song; Chuanzhu Lv; Guoqiang Zhang; Huiqiong Tan; Yu Ma; Yimin Zhu; Xiaotong Han; Chaoqian Li; Shengtao Yan; et al. (Journal of Hazardous Materials, 2023)

How does digitalization drive carbon emissions? The inverted U-shaped effect in China - Ruijing Zheng; Ge Wu; Yu Cheng; Haimeng Liu; Yaping Wang; Xinyang Wang (Environmental Impact Assessment Review, 2023)

Phase engineering of 1 T-MoS2 on BiVO4 photoanode with p–n Junctions: Establishing high speed charges transport channels for efficient photoelectrochemical water splitting - Lianqing Yu; Kehui Xue; Huihua Luo; Chong Liu; Heyuan Liu; Haifeng Zhu; Yaping Zhang (Chemical Engineering Journal, 2023)

Au loaded mesoporous SiO2/gelatin hydrogel: Detecting low humidity and NH3 - Zhiyan Ma; Yunlong Yu; Ke Wu; Yaping Song; Sen Liu; Xi Yang; Teng Fei; Tong Zhang (Chemical Engineering Journal, 2023)

Highly efficient catalytic degradation of dicamba using Fe3O4/montmorillonite composite: Mechanism and toxicity assessment - Yu Ouyang; Guangyong Zeng; Wei Zhu; Xuemei Yao; Mengyun Yang; Xiuyu Long; Jie Zheng; Yaping Tao; Yaocheng Deng; Chunxia Ding (Process Safety and Environmental Protection, 2023)

Design, synthesis and biological evaluation of aminopyrimidine derivatives bearing dihydroquinoxalinone as novel EGFRL858R/T790M kinase inhibitors against non-small-cell lung cancer - Liping Fu; Yu Cao; Jingbai Chen; Ruoyu He; Yanmei Zhao; Yaping Zhao; Jianjun Xi; Rangxiao Zhuang; Chongmei Tian (Medicinal Chemistry Research, 2023)

Independent and combined effects of exposure to organophosphate esters on thyroid hormones in children and adolescents - Liqin Hu; Bin Zhou; Yaping Li; Lulu Song; Jin Wang; Meng Yu; Xiang Li; Ling Liu; Jing Kou; Youjie Wang; Xijiang Hu; Surong Mei (Environmental Geochemistry and Health, 2023)

Elevated CO2 and temperature increase arbuscular mycorrhizal fungal diversity, but decrease root colonization, in maize and wheat - Zihao Liu; Zhenhua Yu; Bin Song; Yansheng Li; Jie Fang; Yaping Guo; Jian Jin; Jonathan M. Adams (Science of The Total Environment, 2023)

New insights into membrane fouling during direct membrane filtration of municipal wastewater and fouling control with mechanical strategies - Yu Men; Zifu Li; Lixin Zhu; Xuemei Wang; Shikun Cheng; Yaping Lyu (Science of The Total Environment, 2023)

Simultaneous recovery of nutrients and water from human urine by a novel thermally activated peroxydisulfate and membrane distillation integrated system - Yaping Lyu; Xiuwei Ao; Shikun Cheng; Nana Liu; Yu Men; Zifu Li (Chemical Engineering Journal, 2023)

A new risk factor associated with cardiovascular disease: clonal hematopoiesis of indeterminate potential - Xiongkai Yu; Ningjing Qian; Yaping Wang (Molecular Biology Reports, 2023)

Gastrodin ameliorates exercise-induced fatigue via modulating Nrf2 pathway and inhibiting inflammation in mice - Yaping Zhou; Qi Wu; Wen Yu; Fan Ye; Yunyun Cao; Otobong D. Akan; Xiuxiu Wu; Tiantian Xie; Han Lu; Fuliang Cao; Feijun Luo; Qinlu Lin (Food Bioscience, 2023)

Conceptual design of long span steel-UHPC composite network arch bridge - Yaping Lai; Yu Li; Maoke Huang; Lijun Zhao; Jiayong Chen; Yi Min Xie (Engineering Structures, 2023)

Assessment of Fungal Diversity in Minqin County, a Typical Arid Region in Northwestern China - Zhanwu Peng; Shuwei Wei; Yaping Hu; Bao Qi; Chaofeng Yuan; Qi Wang; Yu Li (Current Microbiology, 2023)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Identifying the influencing factors and constructing incentive pattern of residents’ waste classification behavior using PCA-logistic regression - Ruijing Zheng; Mengqi Qiu; Yaping Wang; Deyang Zhang; Zeping Wang; Yu Cheng (Environmental Science and Pollution Research, 2022)

Enhanced Influenza Immunity by Nasal Mucosal Administration of the TPGS-Modified Liposomal Vaccine - Shijie Ma; Rui Yu; Yaping Mai; Na Yu; Ting Gao; Jianhong Yang (AAPS PharmSciTech, 2022)

Impact of human capital on the green economy: empirical evidence from 30 Chinese provinces - Xinyang Wang; Yaping Wang; Ruijing Zheng; Jingjing Wang; Yu Cheng (Environmental Science and Pollution Research, 2022)

A New Dual-peak Fluorescent Probe for Water Content Detection Made From Taxus - Gang Wang; Yaping Li; Haipeng Chen; Shuqin Tang; Yiyang Cheng; Yuhong Yu; Abdul Qayoom Majeedano; Shangrao Pu; Gang Wang (Journal of Fluorescence, 2022)

Regulation of wound healing and fibrosis by galectins - Dong Yu; Ming Bu; Ping Yu; Yaping Li; Yang Chong (Journal of Molecular Medicine, 2022)

Organophosphate esters in children and adolescents in Liuzhou city, China: concentrations, exposure assessment, and predictors - Meng Yu; Xiang Li; Bingqing Liu; Yaping Li; Ling Liu; Limei Wang; Lulu Song; Youjie Wang; Liqin Hu; Surong Mei (Environmental Science and Pollution Research, 2022)

Biological monitoring and health assessment of 21 metal(loid)s in children and adolescents in Liuzhou City, Southwest China - Yaping Li; Yu Zhang; Meng Yu; Liqin Hu; Ting Zeng; Ling Liu; Limei Wang; Liangqiong Deng; Xiang Li; Ping Liu; Dingyuan Zeng; Surong Mei (Environmental Science and Pollution Research, 2022)

Enhancement of oral bioavailability and anti-hyperuricemic activity of aloe emodin via novel Soluplus®—glycyrrhizic acid mixed micelle system - Feng Shi; Lin Chen; Yaping Wang; Jing Liu; Michael Adu-Frimpong; Hao Ji; Elmurat Toreniyazov; Qilong Wang; Jiangnan Yu; Ximing Xu (Drug Delivery and Translational Research, 2022)

Path dependence in pro-poor tourism - Yaping Liu; Jie Yu (Environment, Development and Sustainability, 2022)

Anaerobic semi-fixed bed biofilm reactor (An-SFB-BR) for treatment of high concentration p-nitrophenol wastewater under shock loading conditions - Maolian Chen; Ningning Yu; Yaping Chen; Qibang Tong; Yong Guo (Biodegradation, 2021)

Decreased grain size1, a C3HC4-type RING protein, influences grain size in rice (Oryza sativa L.) - Xingjie Zhu; Shengzhong Zhang; Yaping Chen; Changlin Mou; Yunshuai Huang; Xi Liu; Jingli Ji; Jiangfeng Yu; Qixian Hao; Chunyan Yang; Mengying Cai; Thanhliem Nguyen; et al. (Plant Molecular Biology, 2021)

A Fluorescent “Turn-off” Probe for the Determination of Curcumin Using Upconvert Luminescent Carbon Dots - Chenhong Yu; Qi Zhuang; Hanyue Cui; Li Li; Yaping Ding; Jiaxin Lin; Yingchun Duan (Journal of Fluorescence, 2020)

Gene UCHL1 expresses specifically in mouse uterine decidual cells in response to estrogen - Lishuang Hao; Di Song; Mengfei Zhuang; Yan Shi; Lin Yu; Yaping He; Jian Wang; Tingting Zhang; Zhaogui Sun (Histochemistry and Cell Biology, 2020)

How does energy poverty affect economic development? A panel data analysis of South Asian countries - Asad Amin; Yaping Liu; Jie Yu; Abbas Ali Chandio; Samma Faiz Rasool; Ji Luo; Shah Zaman (Environmental Science and Pollution Research, 2020)

Generation of mice with hepatocyte-specific conditional deletion of sphingosine kinase 1 - Jinfeng Yu; Jiale Dong; Kangdi Chen; Yaping Ding; Zhicheng Yang; Tian Lan (Transgenic Research, 2020)

ATM-deficient lung, prostate and pancreatic cancer cells are acutely sensitive to the combination of olaparib and the ATR inhibitor AZD6738 - Nicholas R. Jette; Suraj Radhamani; Ruiqiong Ye; Yaping Yu; Greydon Arthur; Siddhartha Goutam; Tarek A. Bismar; Mehul Kumar; Pinaki Bose; Steven Yip; Michael Kolinsky; Susan P. Lees-Miller (Genome Instability & Disease, 2020)
The Ataxia Telangiectasia Mutated (ATM) protein kinase is mutated in several human cancers, presenting potential opportunities for targeted cancer therapy. We previously reported that the poly-ADP-ribose polymerase (PARP) inhibitor olaparib induces transient G2 arrest but not cell death in ATM-deficient lung cancer cells, while the combination of olaparib with the ATM- and Rad3-related (ATR) inhibitor VE-821 induced cell death. Here, we show that combination of olaparib plus the clinically relevant ATR inhibitor AZD6738 also induces cell death in ATM-deficient lung, prostate and pancreatic cancer cells with little effect on their ATM-proficient counterparts. Together, our data suggest that lung, prostate and pancreatic patients whose tumours exhibit loss or inactivation of ATM may benefit from combination of a PARP inhibitor plus an ATR inhibitor.

Sodium-induced solid-phase hydrogenation of carbon dioxide to formate by mechanochemistry - Dunfan Zhou; Meng Yu; Yaping Fan; Zhenyu Wang; Guoju Dang; Quansheng Zhang; Jingying Xie (Environmental Chemistry Letters, 2020)

Comparative physiological and metabolomic analyses reveal natural variations of tulip in response to storage temperatures - Yanping Wang; Huimin Zhao; Yaping Wang; Siyuan Yu; Yuchao Zheng; Wen’en Wang; Zhulong Chan (Planta, 2019)

Comparative genomics for non-O1/O139 Vibrio cholerae isolates recovered from the Yangtze River Estuary versus V. cholerae representative isolates from serogroup O1 - Li Gong; Pan Yu; Huajun Zheng; Wenyi Gu; Wei He; Yadong Tang; Yaping Wang; Yue Dong; Xu Peng; Qunxin She; Lu Xie; Lanming Chen (Molecular Genetics and Genomics, 2019)

Olfactory-ensheathing cells promote physiological repair of injured recurrent laryngeal nerves and functional recovery of glottises in dogs - Hongyi Liu; Yu Pu; Yaping Xu; He Xu; Huanhai Liu; Yin Cheng; Weihua Xu; Xiaoping Chen; Jingping Fan (Molecular and Cellular Biochemistry, 2018)

Stocks and dynamics of particulate and dissolved organic matter in a large, shallow eutrophic lake (Taihu, China) with dense cyanobacterial blooms - Limei Shi; Yaxin Huang; Yaping Lu; Feizhou Chen; Min Zhang; Yang Yu; Fanxiang Kong (Journal of Oceanology and Limnology, 2018)

A rapid method for establishment of a reverse genetics system for canine parvovirus - Yongle Yu; Jun Su; Jigui Wang; Ji Xi; Yaping Mao; Qiang Hou; Xiaomei Zhang; Weiquan Liu (Virus Genes, 2017)

Temporal and spatial variations of aquatic environmental characteristics and sediment bacterial community in five regions of Lake Taihu - Yu Wan; Yang Bai; Jia He; Yaping Zhang; Rongfu Li; Xiaohong Ruan (Aquatic Ecology, 2017)

Assessing the vulnerability of changing coasts, Hainan Island, China - Yaping Wang; Benwei Shi; Liang Zhang; Jianjun Jia; Xiaomin Xia; Liang Zhou; Rui Yu; Yang Yang; Jianhua Gao (Acta Oceanologica Sinica, 2017)

Alterations of Synaptic Proteins in the Hippocampus of Mouse Offspring Induced by Developmental Lead Exposure - Haiyang Yu; Yingjun Liao; Tingting Li; Yan Cui; Gaoyang Wang; Fenghong Zhao; Yaping Jin (Molecular Neurobiology, 2016)

Environmental filtering decreases with fish development for the assembly of gut microbiota - Qingyun Yan; Jinjin Li; Yuhe Yu; Jianjun Wang; Zhili He; Joy D. Van Nostrand; Megan L. Kempher; Liyou Wu; Yaping Wang; Lanjie Liao; Xinghao Li; Shu Wu; et al. (Environmental Microbiology, 2016)
Summary Gut microbiota typically occupy habitats with definable limits/borders that are comparable to oceanic islands. The gut therefore can be regarded as an ‘island’ for the assembly of microbial communities within the ‘sea’ of surrounding environments. This study aims to reveal the ecological mechanisms that govern microbiota in the fish gut ‘island’ ecosystem. Taxonomic compositions, phylogenetic diversity, and community turnover across host development were analyzed via the high‐throughput sequencing of 16S rRNA gene amplicons. The results indicate that the Shannon diversity of gut microbiota in the three examined freshwater fish species all significantly decreased with host development, and the dominant bacterial taxa also changed significantly during host development. Null model and phylogenetic‐based mean nearest taxon distance (MNTD) analyses suggest that host gut environmental filtering led to the assembly of microbial communities in the fish gut ‘island’. However, the phylogenetic clustering of local communities and deterministic processes that governed community turnover became less distinct as the fish developed. The observed mechanisms that shaped fish gut microbiota seemed to be mainly shaped by the gut environment and by some other selective changes accompanying the host development process. These findings greatly enhance our understanding of stage‐specific community assembly patterns in the fish gut ecosystem.

Genetic characterization of the complete genome of an Aleutian mink disease virus isolated in north China - Ji Xi; Jigui Wang; Yongle Yu; Xiaomei Zhang; Yaping Mao; Qiang Hou; Weiquan Liu (Virus Genes, 2016)

Comparison of biological and genomic characteristics between a newly isolated mink enteritis parvovirus MEV-LHV and an attenuated strain MEV-L - Yaping Mao; Jigui Wang; Qiang Hou; Ji Xi; Xiaomei Zhang; Dawei Bian; Yongle Yu; Xi Wang; Weiquan Liu (Virus Genes, 2016)

A Fluorescent Switch Sensor for Glutathione Detection Based on Mn-doped CdTe Quantum Dots - Methyl Viologen Nanohybrids - Lurong Yu; Li Li; Yaping Ding; Yaxiang Lu (Journal of Fluorescence, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Fingolimod alters inflammatory mediators and vascular permeability in intracerebral hemorrhage - Yu-Jing Li; Guo-Qiang Chang; Yuanchu Liu; Ye Gong; Chunsheng Yang; Kristofer Wood; Fu-Dong Shi; Ying Fu; Yaping Yan (Neuroscience Bulletin, 2015)

High-level expression and characterization of a thermophilic β-mannanase from Aspergillus niger in Pichia pastoris - Shi Yu; Zhezhe Li; Yaping Wang; Wanping Chen; Lin Fu; Wei Tang; Chen Chen; Yunyun Liu; Xue Zhang; Lixin Ma (Biotechnology Letters, 2015)

A Simple Fluorescence Quenching Method for the Determination of Vanillin Using TGA-capped CdTe/ZnS Nanoparticles as Probes - Li Li; Qiaolin Zhang; Yaping Ding; Yaxiang Lu; Xiaoyong Cai; Lurong Yu (Journal of Fluorescence, 2015)

FLT3 and CDK4/6 inhibitors: Signaling mechanisms and tumor burden in subcutaneous and orthotopic mouse models of acute myeloid leukemia - Yaping Zhang; Cheng-Pang Hsu; Jian-Feng Lu; Mita Kuchimanchi; Yu-Nien Sun; Ji Ma; Guifen Xu; Yilong Zhang; Yang Xu; Margaret Weidner; Justin Huard; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Transcriptome Profile Analysis of Maize Seedlings in Response to High-salinity, Drought and Cold Stresses by Deep Sequencing - Xiaohui Shan; Yidan Li; Yu Jiang; Zhilei Jiang; Wenyuan Hao; Yaping Yuan (Plant Molecular Biology Reporter, 2013)

Inhibition of Camellia sinensis (L.) O. Kuntze on Microcystis aeruginosa and isolation of the inhibition factors - Yaping Lu; Jin Wang; Yang Yu; Wen Su; Fanxiang Kong (Biotechnology Letters, 2013)

Spontaneous uptake of exogenous DNA by goat spermatozoa and selection of donor bucks for sperm-mediated gene transfer - Yongju Zhao; Mingju Yu; Lingbin Wang; Yaofeng Li; Jingsheng Fan; Qian Yang; Yaping Jin (Molecular Biology Reports, 2012)

Determination of Paracetamol Based on its Quenching Effect on the Photoluminescence of CdTe Fluorescence Probes - Li Li; Yaxiang Lu; Yaping Ding; Yu Cheng; Wanchen Xu; Fenfen Zhang (Journal of Fluorescence, 2012)

Association between polymorphisms in the signal transducer and activator of transcription and dilated cardiomyopathy in the Chinese Han population - Ying Peng; Bin Zhou; Yanyun Wang; Yu Chen; Hui Li; Yaping Song; Lin Zhang; Li Rao (Molecular and Cellular Biochemistry, 2012)

Effects of exogenous glutathione on arsenic burden and NO metabolism in brain of mice exposed to arsenite through drinking water - Yan Wang; Fenghong Zhao; Yaping Jin; Yuan Zhong; Xiaoyun Yu; Gexin Li; Xiuqiang Lv; Guifan Sun (Archives of Toxicology, 2011)

Novel parvovirus sublineage in the family of Parvoviridae - Fang Wang; Yongwei Wei; Chun Zhu; Xianbo Huang; Yaping Xu; Lian Yu; Xuping Yu (Virus Genes, 2010)

Design of Two Pyrazole-Based Sensors with Similar Configuration and Different Fluorescent Response to Anions - Yaping Li; Jie Shao; Xudong Yu; Xiufang Xu; Hai Lin; Zunsheng Cai; Huakuan Lin (Journal of Fluorescence, 2010)

Effects of in utero meso-2,3-dimercaptosuccinic acid with calcium and ascorbic acid on lead-induced fetal development - Fei Yu; Yingjun Liao; Yaping Jin; Yue Zhao; Yahao Ren; Chunwei Lu; Gexin Li; Yanxi Li; Jun Yang (Archives of Toxicology, 2008)

Maternal cigarette smoking, metabolic gene polymorphisms, and preterm delivery: new insights on G×E interactions and pathogenic pathways - Hui-Ju Tsai; Xin Liu; Karen Mestan; Yunxian Yu; Shanchun Zhang; Yaping Fang; Colleen Pearson; Katherin Ortiz; Barry Zuckerman; Howard Bauchner; Sandra Cerda; Phillip G. Stubblefield; et al. (Human Genetics, 2008)

Therapeutic potentials of combined use of DMSA with calcium and ascorbic acid in the treatment of mild to moderately lead intoxicated mice - Yingjun Liao; Jun Zhang; Yaping Jin; Chunwei Lu; Gexin Li; Fei Yu; Xuping Zhi; Li An; Jun Yang (BioMetals, 2008)

Selection of micronutrients used along with DMSA in the treatment of moderately lead intoxicated mice - Yingjun Liao; Fei Yu; Yaping Jin; Chunwei Lu; Gexin Li; Xuping Zhi; Li An; Jun Yang (Archives of Toxicology, 2008)

Increasing the transient expression of GUS gene in Porphyra yezoensis by 18S rDNA targeted homologous recombination - Hongquan Liu; Wengong Yu; Jixun Dai; Qianhong Gong; Kunfeng Yang; Yaping Zhang (Journal of Applied Phycology, 2003)

Multiple origins of Tibetan Y chromosomes - Yaping Qian; Binzhi Qian; Bing Su; Jiankun Yu; Yuehai Ke; Zhengtao Chu; Lei Shi; Daru Lu; Jiayou Chu; Li Jin (Human Genetics, 2000)